The Education of Labour in the United States - Jolicoeur, Fernand (Relations industrielles / Industrial Relations, 1952)
SummaryIn a general picture of the education of labour in the United States of which the evolution has followed that of American unionism, this study gives an idea of the conception that the American unions have of the education of labour and the methods they use to carry it out. The Author asserts that they attach much importance to the training of their members in union questions, but do not go any further except in particular cases. They have developed, however, techniques in adult education which could serve efficiently for a much wider formation.